Kepuasan Kerja SMA Negeri di Kota Kupang - Nusa Tenggara Timur - Lao, Hendrik A.E (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2018)
The Objective of this study was to recognize the influence of teachers professional competence toward job satisfactions, influence of school culture toward job satisfactions and combination the influence of teachers professional competence and school culture toward job satisfactions. The research method used was a quantitative research method with a sample of 215 teachers who are representative of each subject chosen in a proportional random sampling. The data were collected with instruments that have been tested for validity and reliability for independent variables of both school cultures and job satisfaction dependent variables while the first independent variables of teachers professional competence were derived from the results of online teachers competence test. Result of research: 1) there was significant influence of teachers professional competence toward job satisfactions equal to R2 = 0,047 = 4,7%; 2) there was significant influence of school culture on job satisfactions equal to R2 = 0, 513 = 51,3%, 3) the combination of professional competence and school culture there was significant influence on job satisfactions equal to R2 = 0,522 = 52,2%.